Anticancer Potential and Other Therapeutic Activities of Curcumin & Its Derivatives - Rajiv Kumar; Rajan Salwan.; Nitish Sharma; Arshdeep Singh; Diksha Kumari; Rajbir Singh; Mukesh Chander (Emerging Trends in Metabolites, 2026)
Curcumin, a compound isolated from turmeric, is used in the management of various diseases due to its extensive medicinal properties. Curcumin, the principal polyphenol isolated from Curcuma longa (turmeric), has garnered immense scientific interest for its extensive medicinal properties, including potent anti-inflammatory, antioxidant, and anticancer activities demonstrated in preclinical models. An expanding body of research indicates broad therapeutic promise in managing diverse pathologies, from various cancers to chronic inflammatory, metabolic, and dermatological conditions. However, a significant paradox limits its clinical translation: this vast in vitro potential is almost completely nullified by catastrophic pharmacokinetic failures. This review deconstructs this “curcumin paradox.”An expanding body of research indicates that curcumin may hold promise as a therapeutic agent in the management of various dermatological conditions. It possesses anticancer activity by suppressing proliferation and metastasis and by promoting cell cycle arrest or apoptosis in various cancer cells. Despite all these benefits, the therapeutic application of curcumin in clinical medicine and its bioavailability are still impaired by its poor absorption and rapid metabolism. The combination of curcumin with novel delivery systems represents a highly promising area for future applied research.
Keywords: COVID-19; Psoriasis; Wound Care; anti-arthritis; anticancer; antioxidants